Optimalisasi Daya Output Solar Photovoltaic Dengan Sistem Dual Axis Sun Tracker Berbasis Microcontroller - Jamarrintan Jamarrintan; Iswadi Hasyim Rosma (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Solar photovoltaic (SPV) is one of renewable energy sources that has been used widely during past decades. Generally, SPV panels are installed at certain titled angle. This method of installation has its own disadvantage, such as when the sun moves away from the SPV panel, the energy produced by the SPV panel becomes decreased. Therefore, this article aims to design and utilize the Dual Axis Sun Tracker (DAST) system to overcome these problems. This DAST system uses four LDR sensors as sun position detectors, an Arduino microcontroller is used as controller system and two servo motors are implemented on the vertical axis and horizontal axis in order to move SPV panel to have perpendicular sunlight. The DAST system has been tested and compared to fixe tilted angle SPV panels with 2 conditions, namely the fixed titled angle SPV panel facing east and west, respectively. The tilted angle was also varied with 5 variations, namely 00, 150, 250, 350 and 450. The field data have been collected for 5 days in Pekanbaru city, Indonesia. From the results of the comparison it can be seen that the SPV panel with the DAST system provide much greater energy gain compared to fixed titled angle SPV panel.Keywords: Arduino, Dual Axis Sun Tracker, Energy, Solar Photovoltaic, Sun Tracking System